2005
DOI: 10.1161/01.str.0000185653.49740.c6
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Administration of a New Free Radical Scavenger, Edaravone, Is More Effective Than its Long-Term Administration for the Treatment of Neonatal Hypoxic–Ischemic Encephalopathy

Abstract: Background and Purpose-Edaravone (3-methyl-1-phenyl-2-pyrazolin-5-one) is a new free radical scavenger that is used for the treatment of adult acute cerebral infarction in Japan. We examined the effect of edaravone on the optimal duration of treatment, the long-term effect on the brain, and the effect on learning and memory disability in a rat model of neonatal hypoxic-ischemic encephalopathy. Methods-Seven-day-old Wistar rats were subjected to left common carotid artery ligation then 2 hours of hypoxicischemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 28 publications
2
31
0
3
Order By: Relevance
“…In this connection, it is very interesting to consider DNA peroxidation from the standpoint of oxidation stress pathology. It is already reported that 2-d edaravone treatment is more effective than 5-d or 10-d treatment in this model (26). We also showed that 8-OHdG overexpression correlated to apoptotic neuronal cell death within 48 h after HI insult.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In this connection, it is very interesting to consider DNA peroxidation from the standpoint of oxidation stress pathology. It is already reported that 2-d edaravone treatment is more effective than 5-d or 10-d treatment in this model (26). We also showed that 8-OHdG overexpression correlated to apoptotic neuronal cell death within 48 h after HI insult.…”
Section: Discussionsupporting
confidence: 74%
“…The same dose of edaravone or normal saline was then administered every 24 h until being killed. The dose and time course of edaravone were based on the previous data (26). Rat pups were killed 6, 24, 48, and 72 h after HI insult.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, short term administration of this drug was reported to be more effective than its long term use [67].…”
Section: Reactive Oxygen Speciesmentioning
confidence: 99%
“…If the animal succeeded in swimming to the platform within 120 s and stayed on the platform for 20 s, the animal was considered to have recognized the location of the platform, and the measurement was completed. For any animal which failed to swim to the platform within 120 s, the measurement was terminated, the goal latency was recorded as 120 s, and the animal was gently placed on the platform for 20 s. 9) Working Memory Test The animals were subjected to the Morris water maze test for working memory for 3 d, starting 2 d after the reference memory test. The working memory test was procedurally similar to the reference memory test, except that the platform location was fixed within the test day, but changed each test day.…”
Section: )mentioning
confidence: 99%